Bone augmentation by anatomical region : techniques and decision-making - Artzi, Zvi (Professor of periodontology) (Hoboken, NJ : John Wiley & Sons, 2020)
'Comprehensively describes bone augmentation techniques and their application to the different anatomical regions of the upper and lower jaws. Bone Augmentation by Anatomical Region is a unique, evidence-based guide focusing on each specific anatomical region -- anterior maxilla, posterior maxilla, anterior mandible, and posterior mandible -- in order to emphasize the correct implemented procedures needed to successfully perform oral osseous reconstruction. Numerous ridge augmentation techniques are covered, including: horizontal and vertical guided bone regeneration, autologous block transplantation, interpositional bone grafting, allogeneic blocks, sandwich technique, split-expansion ridge technique, and sinus floor grafting. Non-augmented approaches such as forced socket site extrusion and the installation of digitally printed implants are also presented and discussed. Guides readers on tackling bone augmentation via anatomical region of the jaws and their related surrounding muscles, vascularization and innervation Presents innovative augmentation techniques for the anterior maxilla, posterior maxilla, anterior mandible, and posterior mandible Includes clinical photographs in each section and a decision tree to help readers select the appropriate surgical modality'--
Includes bibliographical references and index.
Keywords: Orthognathic Surgical Procedures -- methods; Bone Regeneration; Bone Transplantation -- methods